2017
DOI: 10.1021/jacs.7b07388
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Total Synthesis of (−)-Pavidolide B

Abstract: The enantioselective synthesis of (-)-pavidolide B (1) was achieved in a linear sequence of 10 steps. The key steps are (a) an enantioselective organocatalytic cyclopropanation; (b) a radical-based cascade annulation for the regio- and diastereo-selective synthesis of the highly functionalized lactone 3 bearing the characteristic tricyclic core and seven contiguous stereocenters;

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
62
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 64 publications
(65 citation statements)
references
References 43 publications
1
62
0
1
Order By: Relevance
“…Theh ighly congested architectures as well as the intriguing biological properties of the sarcophytin family members have stimulated several elegant total syntheses of their core structures and target molecules from the groups of Gçssinger, [4a,e] Deslongchamps, [4b,f-j] Maimone [4c] and Carreira. [5] Preliminary investigation showed that 5 exhibits high selective inhibitory activity against an umber of human promyelocytic leukemia cell lines.T he dome-shaped [6,5,5,7] tetracyclic ring system, especially the fully functionalized cyclopentane core,c ombined with seven contiguous stereogenic centers renders 5 as ynthetic target with significant challenges.M ost recently, an exquisite enantioselective total synthesis toward 5 has been disclosed by Yang,G ong, and co-workers,a nd they employed ac ascade radical annulation of vinylcyclopropane as the key step. [5] Preliminary investigation showed that 5 exhibits high selective inhibitory activity against an umber of human promyelocytic leukemia cell lines.T he dome-shaped [6,5,5,7] tetracyclic ring system, especially the fully functionalized cyclopentane core,c ombined with seven contiguous stereogenic centers renders 5 as ynthetic target with significant challenges.M ost recently, an exquisite enantioselective total synthesis toward 5 has been disclosed by Yang,G ong, and co-workers,a nd they employed ac ascade radical annulation of vinylcyclopropane as the key step.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…Theh ighly congested architectures as well as the intriguing biological properties of the sarcophytin family members have stimulated several elegant total syntheses of their core structures and target molecules from the groups of Gçssinger, [4a,e] Deslongchamps, [4b,f-j] Maimone [4c] and Carreira. [5] Preliminary investigation showed that 5 exhibits high selective inhibitory activity against an umber of human promyelocytic leukemia cell lines.T he dome-shaped [6,5,5,7] tetracyclic ring system, especially the fully functionalized cyclopentane core,c ombined with seven contiguous stereogenic centers renders 5 as ynthetic target with significant challenges.M ost recently, an exquisite enantioselective total synthesis toward 5 has been disclosed by Yang,G ong, and co-workers,a nd they employed ac ascade radical annulation of vinylcyclopropane as the key step. [5] Preliminary investigation showed that 5 exhibits high selective inhibitory activity against an umber of human promyelocytic leukemia cell lines.T he dome-shaped [6,5,5,7] tetracyclic ring system, especially the fully functionalized cyclopentane core,c ombined with seven contiguous stereogenic centers renders 5 as ynthetic target with significant challenges.M ost recently, an exquisite enantioselective total synthesis toward 5 has been disclosed by Yang,G ong, and co-workers,a nd they employed ac ascade radical annulation of vinylcyclopropane as the key step.…”
mentioning
confidence: 99%
“…[4d] In recent isolation studies, 1 and 3 were also identified by Lin and co-workers from Sinularia pavida,a long with (À)pavidolide B( 5)a saminor constituent. [6] Although abiosynthetic origin of 5 based on an intramolecular Michael/aldol process was proposed, [5] we were more intrigued by its distinctive carbon functional pattern similar to that of the sarcophytin family members.W e hypothesized that aC 5(10!11) Wagner-Meerwein rearrangement on the B/C rings of the sarcophytin/chatancin skeleton, which was postulated to be constructed through an transannular Diels-Alder cycloaddition of cembrane, [1a,b,4b,j] might be involved in an alternative biosynthetic pathway to 5. [6] Although abiosynthetic origin of 5 based on an intramolecular Michael/aldol process was proposed, [5] we were more intrigued by its distinctive carbon functional pattern similar to that of the sarcophytin family members.W e hypothesized that aC 5(10!11) Wagner-Meerwein rearrangement on the B/C rings of the sarcophytin/chatancin skeleton, which was postulated to be constructed through an transannular Diels-Alder cycloaddition of cembrane, [1a,b,4b,j] might be involved in an alternative biosynthetic pathway to 5.…”
mentioning
confidence: 99%
See 3 more Smart Citations